Aktivitas Antiradikal Krim Ekstrak Tanaman Gonda (Sphenoclea zeylanica Gaertn) dengan Metode DPPH (1,1-diphenyl-2-picrylhydrazyl) - Ni Kadek Vinka Lionita; Ni Putu Wintariani; Dewi Puspita Apsari (Jurnal Ilmiah Medicamento, 2023)
Free radicals are compounds that trigger the premature aging process. The development of Gonda plant extract cream (Sphenoclea zeylanica Gaertn), which contains active antioxidant substances that can fight free radicals, is carried out. The aims of this study were to determine the phytochemical compounds of the 96% ethanol extract of the Gonda (Sphenoclea zeylanica Gaertn) plant, to observe the physical and chemical properties of the cream of the Gonda (Sphenoclea zeylanica Gaertn) plant extract and its potential as an antioxidant through an antiradical test using the DPPH method. This study was an experimental study with four cream formulations and various extract concentrations consisting of 0% (F0), 5% (F1), 10% (F2), and 15% (F3). Evaluation of the physical and chemical properties carried out was the organoleptic test, homogeneity test, spreadability test, viscosity test, adhesion test, pH test, and antiradical activity, which was tested using the DPPH method. The results showed that the 96% ethanol extract of the Gonda plant (Sphenoclea zeylanica Gaertn) positively contained flavonoids, saponins, tannins, steroids, and alkaloids. Gonda plant extract cream (Sphenoclea zeylanica Gaertn) has good physical-chemical properties based on cream evaluation tests. It shows anti-radical activity on average F0 is 596.08 in the very weak category, F1 (5%) is 95.32 in the strong category, F2 (10%), i.e., 64.58 in the strong category, F3 (15%), i.e., 40.96 in the very strong category, and the average positive control is 22.74 in the very strong category. The 96% ethanol extract of the gonda plant as an active ingredient in cream preparations has the potential to be developed into a topical antioxidant, and its antioxidant activity needs to be further investigated in vitro and in vivo.